2012
DOI: 10.5923/j.scit.20110101.01
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Evaluation of Physical Effort in Bass Drum Pedal Drive by Thermography

Abstract: The bass drum is driven by a pedal that promotes muscle fatigue and can cause injuries. In order to provide engineers with valuable tools, this research aimed at analyzing the use of the drum pedal and to evaluate qualitatively the muscle groups involved and their possible relationship with any injuries resulting from fatigue. Through the analysis, it was found that striking the drum pedal provides health risks; therefore, some actions were suggested to avoid injuries to drummers. All data collected can be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Although several studies have examined the biomechanics and motor control of drumming (e.g., Fujii et al, 2009 , 2011 ; Dahl, 2011 ; Chong et al, 2016 ; Mutio et al, 2017 ; Eriksen et al, 2018 ), only three have examined this data in the context of injury prevention. Salvalaio et al (2011) used thermography to examine leg muscle activation in one drummer during two double-kick pedal techniques. Based on the thermographic profiles, the authors concluded that both techniques were likely to lead to muscular fatigue and repetitive stress injuries with prolonged use.…”
Section: Injury Preventionmentioning
confidence: 99%
“…Although several studies have examined the biomechanics and motor control of drumming (e.g., Fujii et al, 2009 , 2011 ; Dahl, 2011 ; Chong et al, 2016 ; Mutio et al, 2017 ; Eriksen et al, 2018 ), only three have examined this data in the context of injury prevention. Salvalaio et al (2011) used thermography to examine leg muscle activation in one drummer during two double-kick pedal techniques. Based on the thermographic profiles, the authors concluded that both techniques were likely to lead to muscular fatigue and repetitive stress injuries with prolonged use.…”
Section: Injury Preventionmentioning
confidence: 99%
“…Thus, the Tsk alterations may provide information about post-exercise recovery, and musculoskeletal overload. Infrared thermography is a non-invasive and non-radioactive evaluation capable of detecting changes in Tsk (Merla et al, 2009;Fournet, Redortier, & Hevenith, 2015;Salvalaio, Silva, Pinho, & Pohlmann, 2011), which can assist in therapeutic decisions regarding the physical condition of athletes (Sillero-Quintana, Gomez-Carmona, & Fernandez-Cuevas, 2017;Ferreira et al, 2008;Côrte & Hernandez, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Musicians generally possess athletic similarities, with repetitive movements and high oxygen consumption (VO2) demands. Oftentimes they require a high metabolic demand in order to perform their specific instruments in a fast-paced, long duration, and intermittent environment (De La Rue, Draper, Potter, & Smith, 2013;Holmes & Redding, 2001;Iñesta, Terrados, Garia, & Perez, 2008;Mulcahy et al, 1990;Nietzsche, Stutzig, Walther, & Siebert, 2015;Robertson, Federoff, & Eisensmith, 2010;Salvalaio, Silva, Pinho, & Pohlmann, 2011;Smith, Burke, Draper, & Potter, 2008). Due to the increased beats·min -1 of their genre's songs, a heavy metal musician must presumably sustain a particularly high metabolic rate when playing.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the increased beats·min -1 of their genre's songs, a heavy metal musician must presumably sustain a particularly high metabolic rate when playing. Drummers require stamina, speed, and quickness within varying bouts of time with simultaneous use of the arms and legs (De La Rue et al, 2013, Salvalaio et al, 2011, Smith et al, 2008. Drumming has been classified as an intermittent movement activity with varying bouts of intensity (De La Rue et al, 2013;Tigerstedt & Olin, 1924).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation